Educational investment, technological innovation, and atmospheric environmental ffficiency: evidence from SBM-DEA and quantile regression model - Ji, Bei; Zhang, Qiong; Liu, Lingyan; Ding, Lei (Frontiers in Environmental Science, 2025)
IntroductionThe scientific measurement of urban atmospheric environmental efficiency is a vital prerequisite for achieving air pollution control and regional green high-quality development.MethodsBased on the data of 11 cities in Zhejiang Province from 2014 to 2022, this study calculates the synergistic governance environmental efficiency (SGEE) of PM2.5 and O3 from both static and dynamic perspectives. Furthermore, a quantile regression model (QRM) is employed to reveal the impact mechanisms of educational investment and technological innovation on the efficiency.ResultsThe results show that: (1) there are significant spatio-temporal variations in the concentrations of PM2.5 and O3 among the 11 cities. The effectiveness of coordinated governance is not significant. (2) The average value of SGEE of PM2.5 and O3 in Zhejiang Province is 0.533. Technological advancement is the primary driving force behind the improvement of the SGEE of PM2.5 and O3. (3) The results of QRM indicate that educational investment primarily improves the SGEE of PM2.5 and O3 at lowefficiency stages, while it exerts a certain resource “Crowding-out effect” at highefficiency stages.In contrast, the rise in the level of technological innovation and the transformation and adjustment of industrial structure can effectively promote the improvement of the SGEE of PM2.5 and O3.DiscussionIn the future, it need strengthen the role of technological innovation in improving the SGEE of PM2.5 and O3.